Legal Responsibility in Resolving Defaults in The Implementation of A Meeting Hall Rental Agreement - Indah Terawati Maharani Putri; Arief Budiono (Universitas Muhammadiyah Surakarta, 2025)
Renting a meeting hall is part of an agreement. The definition of an agreement is an action where someone promises to another person or where two people promise each other to carry out something. This article aims to describe legal responsibilities in resolving defaults on the lease of meeting halls. The research method used in this article is normative juridical, a way of analyzing library materials, namely primary and secondary legal materials. The results of the analysis show that legal efforts that can be taken by one of the injured parties can be resolved through non-litigation or litigation processes. This depends on the agreement between both parties, both the renter and the lessor. If it will go through a non-litigation process such as family peace, negotiation, mediation, consolidation and arbitration. Meanwhile, dispute resolution is through litigation, namely by submitting a case to the Court with the aim of obtaining certainty of permanent legal force and obtaining justice in accordance with applicable law. If deliberations have been held but the lessee does not want to pay or the renting party still feels aggrieved, they can file a lawsuit or claim to the District Court or arbitration on the basis of breach of contract.